PORTO DE VITÓRIA HINTERLAND STUDY FROM 2014 TO 2017 - Coutinho e Silva, Andreia (2020)
Hinterland is an area of influence of a port, and once it is identified, it makes it possible to trace strategies and highlight opportunities for the port growth and development. This study aims to identify the hinterland of Porto Organizado de Vitória, which is an important port complex for the State of Espírito Santo, where through surveys of port movement data, it will be possible to delimit its areas of influence, and with that, seek to identify and understand what are the current challenges faced by the ports of this complex.